Genetic diversity and phylogeography of the Apis bee will mellifera in the islands of the South-west of the Indian Ocean - (:unkn) unknown (My University, 2015)
The South West Indian Ocean (SWIO) islands are home to an exceptional flora and fauna and are considered as one the five most important biodiversity hotspots in the world. In most islands of this region, the honeybee Apis mellifera occupies diverse habitats. Regarding its ability as a generalist pollinator, honeybee interacts with native and highly endemic flora. Furthermore, this species is used by human for beekeeping as it is able to produce honey, pollen and other hive products. Within the large group of bees (Apidae), A. mellifera is a model of diversity that has diverged into several lineages and subspecies in its native range. Among the 28 recognized subspecies, A. m. unicolor has been described as endemic to Madagascar and belongs to the African A lineage. The Mascarenes, Comoros and Seychelles archipelagos surround this continental island but the A. mellifera populations present have been little or never studied. The aims of this thesis were to characterize the honeybee from the Mascarenes (La Réunion, Mauritius, Rodrigues), Comoros (Anjouan, Mohéli, Grande Comore, Mayotte) and Seychelles (Mahé, Praslin, La Digue) archipelagos by determining the evolutionary lineages and subspecies present. Secondly, a study of genetic diversity and structure were conducted on these same insular populations. For that, a large sampling was carried (n = 4095 colonies from the SWIO, and 238 from native continental areas) and was combined to molecular analyzes using mitochondrial markers (sequencing of the COI-COII intergenic region and ND2 gene) and nuclear markers (15 microsatellite loci). Three of the four evolutionary lineages (A, C and M) were detected in different proportions in the 10 studied islands. The African A lineage and A. m. unicolor subspecies were predominant in the SWIO excepted for Rodrigues exclusively from the European C lineage. All sampled colonies from the Seychelles and Comoros archipelagos belong to the African lineage while in La Réu
Keywords: African Research